2011
DOI: 10.1111/j.1600-0714.2011.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent aphthous ulcers—a Toll‐like receptor–mediated disease?

Abstract: Normal TLR architecture prevents inflammatory responses against normal microbes but still contains a deep TLR(+) , PAMP-reactive dormant defense zone. In RAU, the TLR(+), PAMP-reactive zone extends to surface or subsurface exposed to microbial PAMPs. TLR reactivity is further enhanced by recruitment of inflammatory leukocytes forming a new deep line of defense. The organization of the TLR system in healthy mucosa and its changes in RAU are compatible with active pathogenic involvement of TLRs, which together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…TLRs have both pro- and anti-inflammatory properties. While pro-inflammatory TLRs were found to be greatly increased in the epithelium and lamina propria of RAS lesions in some patients 78 , a decrease in expression levels of TLRs with anti-inflammatory activities was also found in another cohort of RAS patients 79 . Therefore, the role of TLRs in RAS pathogenesis still needs to be better defined, but it is possible that an imbalance in pro- and anti-inflammatory activities of TLRs could increase susceptibility to RAS in some individuals.…”
Section: Clinical Manifestation and Pathogenesismentioning
confidence: 89%
“…TLRs have both pro- and anti-inflammatory properties. While pro-inflammatory TLRs were found to be greatly increased in the epithelium and lamina propria of RAS lesions in some patients 78 , a decrease in expression levels of TLRs with anti-inflammatory activities was also found in another cohort of RAS patients 79 . Therefore, the role of TLRs in RAS pathogenesis still needs to be better defined, but it is possible that an imbalance in pro- and anti-inflammatory activities of TLRs could increase susceptibility to RAS in some individuals.…”
Section: Clinical Manifestation and Pathogenesismentioning
confidence: 89%
“…It was found that in patients with RAS, the immune system’s function become disrupted in response to some kind of not yet defined trigger factor, which may include viral and bacterial antigens or stress. In many reports also the role of the autoimmunisation in the disease development was emphasized (Borra et al 2004; Górska 1997b; Hietanen et al 2012; Malmström et al 1983). Both types of the immune response: natural and acquired (humoral and cellular) may become disturbed in patients with RAS, which, among the others, manifests with neutrophils’ reactivation and hyper-reactivity, elevated concentration of the complement ingredients, increased number of NK cells and B lymphocytes, disrupted CD4 + /CD8 + ratio and increased number of CD25 + and T cell receptor (TCR) γδ cells in peripheral blood (Eversole 1997; Lewkowicz et al 2003; Nowak and Górska 2008).…”
Section: Mechanisms Of the Immune Response In Rasmentioning
confidence: 99%
“…Based on previous work suggesting a pathogenic role for oral epithelial cells in RAUs (Al-Samadi et al 2014;Al-Samadi et al 2015), we hypothesized that stimulustriggered sudden and massive apoptotic transepithelial cell death and subsequent secondary necrosis may lead to the release of epithelial cell-derived damage-associated molecular patterns (or danger signals), followed by the sloughing off of the dead epithelial cell layer causing the formation of an epithelial cell ulcer. A rapid and hefty response to such a sudden stress requires the presence and immediate stimulation of a broad spectrum of pattern-recognizing receptors (Hietanen et al 2012). Toll-like receptors (TLRs) represent the bestknown family of such receptors (Kawai and Akira 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Toll-like receptors (TLRs) represent the bestknown family of such receptors (Kawai and Akira 2010). In healthy oral epithelium, these receptors are found only in basal epithelial cells protected by the epithelial cell barrier, whereas in RAUs most are strongly expressed in all epithelial cell layers surrounding the ulcerous tissue defect (Hietanen et al 2012). We therefore hypothesized that the oral epithelial cells may contribute to acute inflammation and pain, not only by actively synthesizing proinflammatory cytokines, but also by passively releasing intracellularly confined danger signals resulting from cell death during secondary necrosis not normally accessible to the cell surface or endosomal TLRs.…”
Section: Introductionmentioning
confidence: 99%